Lithuanian Relics in the Literary Work оf Iоannіkу Halatovskiy and Lazar Baranovich - Юріївна Матушек, Олена (Slavistica Vilnensis, 2009)
In this article, the Kupiatichi icon of the Virgin is considered a literary image in the work ‘Żywoty swętych’ by the Chernigov and Novgorod-Severskiy Archbishop Lazar Baranovich and the work ‘New Heavens’ by the Rector of Kyiv, Mohyla Collegium Ioannikiy Halatovskiy. The miracle stories are analysed as narrative texts in which miracles constitute the main events while the image of the Virgin is studied via the functions it performs as Helper, Protector, Presenter and others.